(untitled) (Acta Scientiarum. Agronomy, 2023)
Citrus represents one of the main fruit crops grown in the world, highlighting the ‘Tahiti’ acid lime tree. The objective was to compare rootstock varieties combined with this scion to identify those with the best agronomic performance and precocity of production, in addition to Phytophthora gummosis resistance. The experiment was carried out in Capitão Poço, northeast region of Pará, and the following seven rootstock genotypes were evaluated: ‘Sunki Tropical’, ‘BRS O S Passos’, ‘BRS Bravo’, ‘BRS Donadio’, ‘Citrandarin Indio’, ‘BRS Matta’, and ‘LVK x LCR-038’. A randomized block experimental design was used, with three replications and 10 plants per plot. The evaluated characteristics were: plant height (m); crown volume (m3); number of ripe fruit per plant; total yield of ripened fruit per plant (kg plant-1); cumulative fruit yield (fruit kg plant-1); and average productive efficiency (fruit kg m-3 of crown). The average productive efficiency was high. For early selection, the best rootstocks in terms of yield, stability and adaptability were Sunki Tropical, BRS O S Passos, and Cintradarin Indio. The fruit number had the greatest direct effect on fruit yield, and crown pruning was directly harmful. Further studies to understand the complex interaction of G x E for BRS Donadio and Sunki Tropical should be carried out.